The Effect of The Israeli and Palestinian War Boycott on Starbucks Financ-es - Sarjono, Haryadi; Khairunnisa, Athalia Shafa; Sandy, Chelsea Anggita Nurramah; Leono, Melfinna; Melisa; Soeratin, Boyke Setiawan (Jurnal Ekonomi Dan Statistik Indonesia, 2024)
The Israel-Palestine conflict has had a significant impact on multinational companies like Starbucks, with boycotts being conducted as a form of protest against alleged support for Israel by Starbucks. The boycott has greatly affected the company's finances, as well as its reputation and overall business expansion. This study aims to assess the financial condition of Starbucks following the boycott phenomenon. The method used in this research is literature review. The collected data shows the extent of Starbucks' financial decline, including not only global sales but also the drop in Starbucks' stock price. Additionally, the study provides information on the reasons behind the boycott and Starbucks' clarifications. Based on the data obtained, Starbucks experienced the longest and steepest stock decline since its IPO, with an 11-day consecutive drop from $107.21 to $93.8906, amounting to approximately $12 billion. This decline reflects investor concerns about the company's sales trends. Starbucks also faced a sales drop of $862.3 million in Q1 2024. Furthermore, the boycott's effects caused Starbucks to delay its expansion and only realize new store openings in Q1 2024. This is because Starbucks focused more on the welfare of its employees and improving sales performance. To mitigate the impact of the boycott, Starbucks can diversify its services, invest in digital technology, and maintain transparent communication to avoid misunderstandings. By taking appropriate and responsive actions, Starbucks can restore sales and consumer trust.